A Rh(ii)/phosphoric acid co-catalyzed three-component reaction of diazo-ketones with alcohols and azonaphthalenes: access to indole derivatives via a formal [3 + 2]-cycloaddition. Issue 48 (10th December 2020) - Yin, Xinru; Xu, Aimin; Hu, Jidi; Bao, Ming; Hu, Wenhao; Qian, Yu
Abstract : Rh(ii )/Phosphoric Acid co-catalyzed muti-component annulation was well established as a new efficient route to construct 1-amino-indole derivatives via dearomatization/rearomatization/cyclization process with in situ formed oxonium ylide. Abstract : A novel dearomatization/rearomatization/cyclization oxonium ylide trapping process is well developed via a dirhodium(ii ) acetate and phosphoric acid cooperatively catalyzed multi-component reaction of diazo-ketones with alcohols and azonaphthalenes. This protocol provides an efficient route to synthesize N -substituted 1-amino-indole derivatives in good yield under mild reaction conditions.